2017
DOI: 10.1186/s13071-017-2295-1
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of Aedes aegypti immature abundance in urban and rural household containers in central Colombia

Abstract: Background Aedes aegypti, the major vector of dengue, breeds in domestic water containers. The development of immature mosquitoes in such containers is influenced by various environmental, ecological and socioeconomic factors. Urban and rural disparities in water storage practices and water source supply may affect mosquito immature abundance and, potentially, dengue risk. We evaluated the effect of water and container characteristics on A. aegypti immature abundance in urban and rural areas. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 54 publications
3
54
0
4
Order By: Relevance
“…Contrary to expectations, this study did not find the significant correlation between containers place and the presence of Aedes sp. This finding was also reported by Overgaard et al [17]. While the result of chi-square examination showed no correlation between container's water sources and the presence of Aedes sp Larvae with p value = >0.999 (p value≥0.05).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Contrary to expectations, this study did not find the significant correlation between containers place and the presence of Aedes sp. This finding was also reported by Overgaard et al [17]. While the result of chi-square examination showed no correlation between container's water sources and the presence of Aedes sp Larvae with p value = >0.999 (p value≥0.05).…”
Section: Discussionsupporting
confidence: 88%
“…Contrary to expectation, this study did not find significant difference between practices water-container draining and the presence of Aedes sp larvae. The result of this research matches with the research conducted by Riandi et al in Tasikmalaya 2017, and it was revealed that there were no significant correlations between the practice of water-container draining and the presence of Aedes sp larvae as shown by p value = 0.099 in Cibunigeulis village [21] while other study conducted by Overgaard found that the frequency of washing container associated with Aedes sp investation, never-washed-container reported four times more likely to be infested than those washed every week [17]. Despite having been drained, there were still moss and dirt on the water container wall.…”
Section: Discussionsupporting
confidence: 86%
“…Another reported the density of mosquitoes in storm drains compared to other settings [80]. Overgaard et al [81] and Unlu et al [82] investigated container characteristics associated with the presence of particular mosquito species. One study evaluated the correlation between mosquito resting habitat and energy accumulation in Florida, US [83].…”
Section: Resultsmentioning
confidence: 99%
“…albopictus to be more common in urban environments compared to rural, and similar results were obtained for Ae. aegypti by Overgaard et al [81], Hagenlocher et al [88] and Silva Lima et al [89]. Fuentes-Vallejo et al [90] compared Ae.…”
Section: Resultsmentioning
confidence: 99%
“…For example, recent studies in Kenya, Columbia and Selangor have shown that there are substantial numbers of Ae. aegypti habitats found in both rural and urban areas [14][15][16].…”
Section: Introductionmentioning
confidence: 99%